The alternative derivation procedure of equations of the law of the junction for the study of the p-n junction theory. Issue 2 (April 2022) - Baskys, Algirdas
The methodology that increases the student interest and provides modern knowledge to the study of the p-n junction theory has been proposed. It is based on two methods: increasing the interest of students using a new approach in derivation of equations of the law of the junction that allows obtaining more comprehensive knowledge about the operation of the p-n junctions and engaging students using the storytelling technique. The reaction of students to the lecture, obtained statistics on the student activity and the results of the student survey show that the proposed methodology allows increasing the student engagement in the p-n junction theory lectures.